Removal efficiency of zinc and copper in synthetic wastewater using constructed wetland - Abdul Zul Afif, Abd Manap (2008)
Constructed wetland has been widely used to provide “natural” ecotechnological treatment solutions for industrial wastewater. Heavy metals such as zinc and copper can cause serious health problem to human and wildlife. The objective of this research is to determine the removal efficiency of zinc and copper in constructed wetland. The scopes of these studies are to study the removal efficiency of zinc and copper as the quantities of plant are increased and to study the effect of pH change in constructed wetland. In this research, the batch mode system of constructed wetland was used and the wetland plant use was water lettuce (pistia stratiotes). For analysis, atomic absorption spectroscopy was used to determine the concentration of zinc and copper. The research was conducted within 7 days of treatment. Each parameter with varying quantity of plants and pH were setup in four containers including control. The control container containing no water lettuce (pistia stratiotes) to compare the effectiveness of constructed wetland using water lettuce (pistia stratiotes). The results for varying quantity of plant for zinc removal are 15 plants achieved highest removal efficiency (74.77 %), followed by 10 plants (69.79 %), 5 plants (32.99 %) and the control (6.06 %). For effect of pH experiment for zinc removal, the result is ph 7 achieved highest removal efficiency (80.41 %), followed by pH 5 (72.22 %), pH 9 (76.47 %) and the control (70.41 %). The results for varying quantity of plant for copper removal are 15 plants achieved highest removal efficiency (90.58 %), followed by 10 plants (86.32 %), 5 plants (81.35 %) and the control (47.95 %). For effect of pH experiment for copper removal, the result is ph 7 achieved highest removal efficiency (93.36 %), followed by pH 5 (92.43 %), pH 9 (85.38 %) and the control (63.47 %). The removal of copper is more effective than zinc removal. As a conclusion, constructed wetland using water lettuce show a good result in removal of zinc and copper in wastewater.